Hedonism as a Decision Factor and Technologic Usage - Arruda Filho, Emílio José Montero; Dholakia, Ruby Roy (Review of Business Management, 2013)
<span style="color: #222222; font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">In the current selection and use of technological products, consumers prefer to adopt products which include new service packages and features. This article presents that all-in-one or integrated products are hedonic but explanation for use thereof is utilitarian. This paper analyzes factors of technological integration, hedonic and utilitarian behavior, in addition to the more traditional environmental factors of price, budget, brand, and choice. All variables presented can be considered decision factors or factors that change preference, given the inclusion of several integrations. Accordingly, we assessed smart phones with different services integrated, such as Internet, wireless, music, video, and camera functions. Our findings support our assertion that consumer preference is based on the integration of product features for both enjoyment and pleasure of use.